Simultaneous fMRI-EEG-Based Characterisation of NREM Parasomnia Disease: Methods and Limitations - Piorecky, Marek; Koudelka, Vlastimil; Miletinova, Eva; Buskova, Jitka; Strobl, Jan; Horacek, Jiri; Brunovsky, Martin; Jiricek, Stanislav; Hlinka, Jaroslav; Tomecek, David; Piorecka, Vaclava (Diagnostics (Basel, Switzerland), 2020)
Functional magnetic resonance imaging (fMRI) techniques and electroencephalography (EEG) were used to investigate sleep with a focus on impaired arousal mechanisms in disorders of arousal (DOAs). With a prevalence of 2-4% in adults, DOAs are significant disorders that are currently gaining attention among physicians. The paper describes a simultaneous EEG and fMRI experiment conducted in adult individuals with DOAs (n=10). Both EEG and fMRI data were validated by reproducing well established EEG and fMRI associations. A method for identification of both brain functional areas and EEG rhythms associated with DOAs in shallow sleep was designed. Significant differences between patients and controls were found in delta, theta, and alpha bands during awakening epochs. General linear models of the blood-oxygen-level-dependent signal have shown the secondary visual cortex and dorsal posterior cingulate cortex to be associated with alpha spectral power fluctuations, and the precuneus with delta spectral power fluctuations, specifically in patients and not in controls. Future EEG-fMRI sleep studies should also consider subject comfort as an important aspect in the experimental design.
Keywords: NREM parasomnia; disorders of arousal; fMRI; simultaneous measurement; EEG